Habitat preferences of foraging rooks Corvus frugilegus during the breeding period in the agricultural landscape of eastern Poland - Kasprzykowski, Zbigniew (Museum & Institute of Zoology, 2003)
The study was carried out in 2000-2002 around 6 rookeries. Rooks foraged in numbers from 1 to 132 birds (n = 417); flocks of less than 10 individuals were dominant. The type of crop influenced the size of a foraging flock. Most of the rooks were recorded within 0.5-1 km of the rookery, while the greatest distance of a foraging ground from the rookery (>> = 2833.3 m) depended on the size of that rookery. Spring corn, meadows and pastureland were of the greatest significance in the rooks foraging area. Winter corn and root crops were avoided, while wasteland areas were visited intermittently.
Bibliogr. p. 30
P. [27]-31 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Rook; birds; Poland; Siedlce; foraging preferences; agricultural landscape; Corvus frugilegus; Corvidae; Aves; 2000-2002

Movement patterns of adult laughing gulls Larus atricilla during the nesting season - Dosch, Jerald J. (Museum & Institute of Zoology, 2003)
The foraging behavior of birds is often influenced by the development and dietary needs of their young. Laughing Gulls in New Jersey, USA, nest in highly productive salt marshes but adults commonly forage at inland sites when they have young in the nest. I monitored movements of individual Laughing Gulls using color-marking, banding and radio-telemetry combined with land-based and aerial surveys. I found that breeding adults were highly mobile and commonly flew inland to forage. Color-marked individuals were observed a mean of 16.6 km and a median of 11.0 km from the colony. Radio-tagged birds were located as far as 40 km inland. Laughing Gulls showed foraging site tenacity both within a given year and from year to year. Radio-tagged adults made as many as 11 foraging trips from the colony per day during both diurnal and nocturnal periods. Activity at the colony peaked during late evening and morning hours. Furthermore, Laughing Gull movement patterns changed with progression of the nesting season. Gulls spent more time at the colony while incubating than during either the chick rearing or fledging periods.
Bibliogr. p. 23-24
P. [15]-25 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Laughing Gull; bird migration; United States; New Jersey; movement; foraging; radio-telemetry; gulls; birds; Larus atricilla; Laridae; Aves; 1992-1994

The effect of trends in ambient temperature on egg volume in the tree sparrow Passer montanus - Barkowska-Sokół, Miłosława (1961– ); Pinowski, Jan (1930– ); Pinowska, Barbara (Museum & Institute of Zoology, 2003)
The effect of ambient temperature before and during laying on egg volume in birds has been studied by many authors. The objective of this paper is to show that trends in daily temperature changes can also influence egg volume. The study was carried out near Warsaw, Poland in 1994 and 1995. We ascertained the laying sequence, size and volume of 1070 eggs in 211 clutches of the Tree Sparrow Passer montanus. The effect of the trend in temperature on the mean egg volume in a clutch explained 0.4% of its variation (0.03% to 4.2%, depending on the brood-period), and the effect of the actual temperature explained 0.9% (0.5% to 1.6% depending on the brood-period). The joint effect of temperature and its trend explained 3.1% (1.7% to 8.9% depending on the brood-period) of variation in the mean egg volume in a clutch. The authors discuss possible mechanisms of the effect of temperature and temperature trend on egg volume.
Bibliogr. p. 11-13
P. [5]-13 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Tree Sparrow; egg-volume; birds; effect of meteorological conditions; ambient temperature; sparrows; Passer montanus; Passeridae; Aves

Re-use of old nests versus the construction of new ones in the magpie Pica pica in the city of Sofia (Bulgaria) - Antonov, Anton (1977–2012); Atanasova, Dimitrinka (Museum & Institute of Zoology, 2003)
Nest re-use in a high density population of Magpies in the City of Sofia and its vicinity was studied during 1999-2000. The rate of nest re-use was significantly higher within the urban area (17%) as compared to the immediate rural surroundings within a distance of 1 km (7%). Re-used nests were on average higher above the ground than newly-built nests. The nest re-use rate was not related to breeding density, abundance or the mean height of available trees. Magpies re-using their old nests laid eggs significantly earlier compared to those building new nests. However, nest re-use did not confer other benefits on the reproductive output since clutch size, hatching and fledging success did not differ significantly between the two nesting strategies.
Bibliogr. p. 4
P. [1]-4 ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Magpie; birds; Bulgaria; Sofia; nest reuse; breeding success; Pica pica; Corvidae; Aves; 1999-2000

Reactions to human disturbances in an urban population of the swan goose Anser cygnoides in Heidelberg (SW Germany) - Randler, Christoph (Museum & Institute of Zoology, 2003)
A total of 127 cases of disturbances were recorded, most of them resulting in not-too-serious reactions. An average disturbance affected 25 geese, occurred at 43 m distance to the cause and lasted 31-60 s. Geese feeding prior to the disturbance reacted more strongly than resting ones, and they were more sensitive to disturbances during the hatching and moulting/flightless period. More than fifty percent of the disturbances were caused by dogs they affected significantly more geese, caused longer durations of disturbances, and probably higher energy costs. There were highly significant positive correlations between a reaction, the duration of a disturbance and the number of geese affected. However, distance to the waterline correlated only with the number of geese affected. Distance to waterline and distance to the source of the disturbance had a high impact on the number of geese affected in a regression model. When disturbances occurred at greater distances, these were more serious, lasted longer and affected more geese. Separate analysis of the dogs demonstrated the influence of dog size (the larger the dog, the greater the disturbance), but not whether it was on a lead. Fleeing into the water was caused by dogs more often than expected. Habituation to an urban environment and predictions for fleeing behaviour are discussed.
Bibliogr. p. 51
P. [47]-52 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Swan Goose; birds; effect of human beings; human disturbances; Germany; Heidelberg; bird-dog disturbances; habituation; feral population; urban environment; Anser cygnoides; Anatidae; Aves; 2002

Habitat structure and breeding parameters of the white stork Ciconia ciconia in the Kolno Upland (NE Poland) - Nowakowski, Jacek J. (Museum & Institute of Zoology, 2003)
An investigation of the habitat structure in nesting territories and the breeding success of the White Stork population in an agriculture landscape of the Kolno Upland adjoining the Biebrza river valley was conducted in 1994-1997. From 85.7% (1997) to 96.8% (1994) of nests were occupied by pairs of storks. The percentage of nests without nestlings was exceptionally low (0%-5.7%). Broods with three nestlings made up the highest proportion, c. 41.7-44.6 % of all the nests occupied by pairs. The average number of nestlings in nests with young was lowest in 1997 (2.53); in 1994-1996 it had been significantly higher (2.84-3.06). Pairs with nests sited up to 100 m from the nearest wet meadows in the river valley have a higher average breeding success in comparison with the pairs whose nests are sited farther away. The White Stork population tended to inhabit the area near the edge of the river valley. In the nesting territories (an area of 1 km radius around the nest site) cereal crops, meadows, green crops, pastures and wet meadows constituted the greatest proportion of the habitat structure. The proportions of these habitat types varied significantly between the nests. There was a significant positive correlation between the number of nestlings raised and the proportion of wet meadows, peat bogs and water bodies in the nesting territories.
Bibliogr. p. 45-46
P. [39]-46 : ill. ; 27 cm
Streszcz. pol. Nazwy taksonów także w jęz. łac.
Abstract in Polish. Taxa in Latin
Keywords: White Stork; birds; breeding biology; Poland; Biebrza; Kolno Upland; breeding success; habitat structure; nesting territories; storks; Ciconia ciconia; Ciconiidae; Aves; 1994-1997

Nest tree utilization by the malabar grey hornbill Ocyceros griseus in the semi-evergreen forest of Mudumalai Wildlife Sanctuary (S India) - Maheswaran, Balaraman; Balasubramanian, Paramasivam (Museum & Institute of Zoology, 2003)
The study was carried out between 2000 and 2002 in a semi-evergreen forest in the south-western portion of the Mudumalai Wildlife Sanctuary, India. A total of 81 cavities in 19 tree species were used for nesting by Malabar Grey Hornbills during the study. Three tree species: Lagerstroemia microcarpa, Terminalia bellirica and T. crenulata together made up 69% of all the nest trees used. The mean height of the nest trees was 36 ą 6 m, girth at breast height 3 ą 1 m and nest height 17 ą 6 m. 35 (67%) nest holes were re-used in 2001 while 21 (40%) nest-holes were re-used in 2002. Terminalia crenulata was the tree re-used most often. Nest fidelity by the Malabar Grey Hornbill was reduced owing to competition by other cavity users.
Bibliogr. p. 36
P. [33]-37 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Malabar Grey Hornbill; birds; breeding biology; India; hole-nesting birds; nest sites; hornbills; Ocyceros griseus; Bucerotidae; Aves; 2000-2002

Temperature dependence of the breeding phenology of the collared flycatcher Ficedula albicollis in the Białowieża Forest (NE Poland) - Mitrus, Cezary (Museum & Institute of Zoology, 2003)
The breeding phenology of Collared Flycatchers was monitored for 7 years (1993 and 1995-2000) in old-growth, oak-lime-hornbeam stands in the primeval Białowieża Forest. In most years, egg laying commenced in the second half of May. The earliest first-egg date (179 broods) was 1 May, the latest such date was 13 May; these dates differed from year to year. The associations between the first-egg date and the mean temperature of the last ten days of April indicated that birds were breeding earlier as a consequence of warmer April temperatures. The earliest hatching date was 21 May, the latest 1 June. Fledging usually started in the first half of June. The length of the breeding season varied from 40 to 53 days and the breeding cycle was negatively related to mean temperature in the first ten days of May.
Bibliogr. p. 75-76
P. [73]-76 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Collared Flycatcher; birds; effect of temperature; Poland; Białowieża Forest; time of breeding; ambient temperature; Old World flycatcher; Ficedula albicollis; Muscicapidae; Aves; 1993-2000

Clutch size and breeding performance of marsh tits Parus palustris in relation to hole size in a primeval forest - Wesołowski, Tomasz (1950– ) (Museum & Institute of Zoology, 2003)
Marsh Tit, a secondary hole nesting bird, was studied in an area with superabundant holes (the primeval forest in the Białowieża National Park, E. Poland). It was not expected to find any relationship between hole size and either clutch size or breeding performance. Analysis of about 350 nest histories collected over 13 years revealed, as expected, no difference between breeding in medium-sized or large holes, but birds using small holes (lowest 25th percentile) laid smaller clutches, fledged marginally fewer young and lost more broods than the birds using the two larger size classes. However, this variation was not due to differences in the timing of laying or the age of females across the hole classes. It is suggested that the use of small holes persisted because of the relatively low fitness energetic costs of making such a sub-optimal choice.
Bibliogr. p. 71-72
P. [64]-72 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Marsh Tit; birds; breeding biology; Poland; Białowieża National Park; Białowieski National Park; nesting success; tree holes; Parus palustris; Poecile palustris; Paridae; Aves

Food of the red-backed shrike Lanius collurio: a comparison of three methods of diet analysis - Tryjanowski, Piotr; Karg, Małgorzata K.; Karg, Jerzy (Museum & Institute of Zoology, 2003)
The diet of the Red-backed Shrike (Lanius collurio) was analysed from collars in nestlings, pellets and prey remains in larders. All the material was collected from the same territories in western Poland.A total of 2855 prey items were identified from all the samples. Insects, mainly Coleoptera, Hymenoptera and Orthoptera, constituted 98.9% of all the prey items identified.In order to determine the diet and predict the impact of food resources on Red-backed Shrike populations, three methods should be used together: pellet content analyses, collar sampling and larder analysis. Our findings suggest that pellet content analysis is an easy and non-invasive method for estimating prey diversity and the frequency index. However, collars are necessary to determine nestling diets. Analyses of prey remains in larders should be used to find large prey, handled before consumption. In a more advanced geographical analysis of the content of the shrike diet, we suggest pooling the data obtained by different methods from the same place, and/or carefully assign methods of diet analyses.
Bibliogr. p. 61-62
P. [59]-63 : ill. ; 27 cm
Streszcz. pol.
Abstract in Polish
Keywords: Red-backed Shrike; birds; nutrition; Poland; Wielkopolska; Great Poland (region); Turew; diet analysis; methods; shrikes; Lanius collurio; Laniidae; Aves; 1999-2000

A survey of the bearded tit Panurus biarmicus during the non-breeding season in a landscape of western Poland - Surmacki, Adrian; Stępniewski, Janusz (Museum & Institute of Zoology, 2003)
The population of Bearded Tit was studied on a 1872 km2 study area of predominantly agricultural landscape in W Poland, near Poznań. During the non-breeding period (October-March) surveys were made every 10-14 days on a sample of 44 marshlands selected at random out of 240 suitable habitat patches found in the study area. Bearded Tits were found at least once in 66% of the patches surveyed, but the average percentage of patches occupied per single survey was 25% and did not vary across the non-breeding season. Re-occupancy of individual reed-bed patches in successive surveys averaged 54% and was lowest during early autumn and in the second half of the winter. 39% of the sites occupied during the winter were used as breeding sites in the spring following or preceding the survey. Of 17 breeding sites, 16 were used by Bearded Tits also outside the breeding season. The numbers of birds recorded peaked in second half of October and declined thereafter. Flock size averaged 3.1 (range 1-55) birds and correlated with total number of Bearded Tits recorded during the single survey. Birds mostly foraged on reed seeds taken from reed ears. Foraging on the ground occurred mostly at the beginning and at the end of non-breeding season. Searching for invertebrates peaked in December-January.
Bibliogr. p. 57-58
P. [53]-58 : ill. ; 27 cm
Abstract in Polish
Keywords: Bearded Tit; birds; Great Poland (region); Poland; Wielkopolska; non-breeding season; foraging; reedbeds; parrotbills; Panurus biarmicus; Paradoxornithidae; Aves; 2000-2001